Real‐world impact of anti‐HER2 therapy‐related cardiotoxicity in patients with advanced HER2‐positive breast cancer. Issue 6 (10th August 2020) - Conduit, C.; de Boer, R. H; Lok, S.; Gibbs, P.; Malik, L.; Loh, Z.; Yeo, B.; Greenberg, S.; Devitt, B.; Lombard, J.; Nottage, M.; Collins, I.; et al.
Abstract: Background: Anti‐HER2 therapy‐related cardiotoxicity is well described in the context of clinical trials, particularly in the setting of early stage disease, but there is more limited data in advanced breast cancer and in the real world setting. Material and methods: A prospectively‐maintained registry database with 312 consecutive patients diagnosed with HER2 positive advanced breast cancer in Australia was analysed. Results: 287 patients (92%) received anti‐HER2 therapy, 17 (6%) experienced anti‐HER2 therapy‐related cardiotoxicity. Patients who experienced cardiotoxicity were more likely to have ≥2 risk factors for cardiotoxicity (OR 3.9 95% CI 1.4‐11.3 p = 0.01). A prior diagnosis of cardiovascular disease was significantly associated with cardiotoxicity (OR 7.1 95% CI 1.3‐39.5). Cardiotoxicity resolved on imaging in 65% of patients; there was no association between severity and resolution. 11 patients (65%) received cardiologist input. Of the patients who developed cardiotoxicity, 12 patients (71%) received further anti‐HER2 therapy in the first‐ or second‐line setting without recurrent cardiotoxicity. Discussion and Conclusion: Therapy‐related cardiotoxicity is an uncommon complication of anti‐HER2 therapy in the real world setting. Cardiac toxicity resolved in the majority of affected patients, and further anti‐HER2 therapy was administered without recurrence of cardiac issues. Our data suggests anti‐HER2 therapy can be safely given in routine care, even in patients with risk factors for toxicity.